Control Chart in the Service Industry: A Case Study in a University Health Clinic - Johan K. Runtuk (International Journal of Science, Technology & Management, 2020)
This study analyzes the service quality of a University health clinic in Bekasi, WestJava, Indonesia. A control chart and capability analysis will be employed to analyzethe services' quality, especially registration processing time and the drug defect permonth. This study uses the CUSUM and EWMA control charts for detecting thesmall shifts in the processing time. The findings revealed that the current processesare in control and capable of meeting the current service level. There is only onepoint outside the upper limit. But it can be ignored/deleted since the assignablecause causes that event. This study gives direction for the Clinic to improve theservice quality.